Antibiotic-induced microbiota depletion impairs the proregenerative response to a biological scaffold - Natalie Rutkowski; Brenda Yang; Elise Gray-Gaillard; Anna Ruta; Joscelyn C. Mejías; Michael Patatanian; Christopher Cherry; Nazmiye Celik; Katlin B. Stivers; Shri Ramanujam; Nathan L. Price; Franck Housseau; et al. (Proceedings of the National Academy of Sciences, 2025)
Therapeutic biological scaffolds promote tissue repair primarily through the induction of type 2 immunity. However, systemic immunological factors, including aging, sex, and previous infections, can modulate this response. The gut microbiota is a well-established modulator of immune function across organ systems, yet its influence on type 2-mediated repair remains underexplored. Here, we establish a bidirectional relationship between the gut microbiota and biological scaffold-mediated tissue repair. Utilizing a conventionalized germ-free mouse, we demonstrate that scaffold implantation induces compositional and functional changes in the gut microbiome, particularly affecting amino acid biosynthesis. Additionally, in a model of antibiotic-induced microbiota depletion, we show that dysbiosis disrupts key immune regulators of type 2 immunity, including reductions in eosinophils, proregenerative macrophages, and interleukin-4 (IL-4)-producing CD4 + T cells. At 6 wk post–scaffold implantation, we observed a significant decrease in myocytes with centrally located nuclei alongside an upregulation in profibrotic gene expression with antibiotic treatment. These findings provide insights into the influence of the gut microbiota on type 2-mediated tissue repair.